Smart covalent organic frameworks and processes derived therefrom for switchable antibacterial activity induced by carbon dioxide adsorption

The process of using carbon dioxide to induce self-detachment of COFs with dimethylamino groups addresses the inefficiencies of existing methods, achieving uniform and energy-efficient nanosheet production with enhanced antibacterial activity.

JP2025508641APending Publication Date: 2025-04-10COUNCIL OF SCI & IND RES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024506671
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-06
Filing Date
2023-01-06
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing methods for removing covalent organic structures (COFs) into ultrathin nanosheets are non-uniform, energy-intensive, and often involve environmentally harmful chemicals, lacking an efficient and environmentally friendly protocol.

Method used

A process utilizing carbon dioxide at ambient temperature and pressure to induce self-detachment of 2D COFs with multiple dimethylamino groups, generating temporary surface charges and resulting in ultrathin nanosheets with adjustable antibacterial activity, which is completely reversible upon heat treatment.

Benefits of technology

Achieves uniform and efficient self-detachment of COFs into ultrathin nanosheets with enhanced antibacterial properties, while being environmentally friendly and energy-efficient, with bacterial growth reduction by over 60% within 30 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508641000010
    Figure 2025508641000010
  • Figure 2025508641000011
    Figure 2025508641000011
  • Figure 2025508641000012
    Figure 2025508641000012
Patent Text Reader

Abstract

The present invention relates to a class of stable 2D covalent organic frameworks bearing multiple dimethylamino groups capable of capturing carbon dioxide at ambient temperature and pressure, as well as an economical and environmentally friendly process for the generation of temporary surface charges and subsequent self-exfoliation of the COFs into ultrathin nanosheets. The exfoliated materials possess activity against pathogenic bacteria. The invention further discloses a carbon dioxide-induced exfoliation process that is fully reversible upon thermal treatment, thereby achieving control over bacterial growth via an efficient antibacterial switch.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to stable 2D covalent organic frameworks [COFs] with multiple dimethylamino groups capable of capturing carbon dioxide at ambient temperature and pressure, and an economical and environmentally friendly process for the generation of temporary surface charges and subsequent self-exfoliation of the COFs into ultrathin nanosheets. The exfoliated materials retain activity against pathogenic bacteria. In particular, the present invention relates to a carbon dioxide-induced exfoliation process that is fully reversible upon thermal treatment, whereby control over bacterial growth is achieved via an efficient antibacterial switch. [Background technology]

[0002] Since the development of single-layer graphene, research on ultrathin two-dimensional (2D) materials has grown exponentially and expanded beyond the realm of graphene (see (a) Zhang, ACS Nano, 2015, 9, 9451; (b) Tan, et al., Chem. Rev., 2017, 117, 6225; (c) M-Balleste, et al., Nanoscale, 2011, 3, 20; (d) Zhuang, et al., Adv. Mater., 2015, 27, 403; (e) Xu, T. Liang, M. Shi, H. Chen, Chem. Rev., 2013, 113, 3766). 2D nanomaterials such as polymer-based nanosheets are similar to graphene and exhibit excellent properties, such as tunable architecture, light weight, flexibility, high surface area, and excellent electronic properties, that make these materials promising candidates for next-generation functional materials (see (a)Thomas, Angew. Chem. Int. Ed., 2010, 49, 8328; (b)Colson, et al., Nat. Chem., 2013, 5, 453; (c)Ding, et al., Chem. Soc. Rev., 2013, 42, 548; (d)Huang, et al., Nat. Rev. Mater., 2016, 1, 16068. (e)Yaghi, et al., Science, 2017, 355, eaal1585). 2D cocalent organic frameworks can offer additional flexibility in terms of designing materials with desired properties (see (a) Bunck, et al., J. Am. Chem. Soc., 2013, 135, 14952; (b) Liu, et al., Adv. Mater., 2014, 26, 6912; (c) Sun, et al., Angew. Chem. Int. Ed., 2017, 57, 1034).

[0003] Concurrent with the development of new and improved functional materials, global climate change and excessive CO2 emissions have raised widespread societal concerns in recent years. Thus, great efforts have been made towards CO2 capture and conversion (see (a)Artz, et al., Chem. Rev. 2018, 118, 434. (b)Sanz-Perez, et al., Chem. Rev. 2016, 116, 19, 11840). As a result, the development of functional porous materials has been continuously increasing over the past decade (see Singh, et al., Chem. Soc. Rev. 2020, 49, 4360) based on reticular chemistry (see Yaghi, J. Am. Chem. Soc. 2016, 48, 15507), leading to the development of two-dimensional (2D) and three-dimensional covalent organic frameworks (COFs) ((a) Cote, et al., Science 2005, 310, 1166; (b) Cote, et al., J. Am. Chem. Soc. 2007, 129, 12914-12915; (c) Wan, et al., Angew. Chem., Int. Ed. 2009, 48, 5439; (d) Ding, et al., Chem. Soc. Rev. 2013, 42, 548; (e) Colson, et al., Nat. Chem. 2013, 5, 453; (f) Waller, et al., Acc. Chem. Res. 2015, 48, 3053-3063) have attracted much attention due to their custom-made structures. However, for this purpose, efficient exfoliation of COFs and the presence of CO2-reactive groups are required.

[0004] Several methods have been used by various research groups worldwide to induce the exfoliation of covalent organic frameworks into 2D nanosheets. Boronate-linked COFs have been reported by condensation reaction of 2,3,6,7,10,11-hexahydroxytriphenylene with 1,3,5-tris[4-phenylboronic acid]benzene and ultrasonication to exfoliate bulk COFs and generate multilayered 2D COF nanostructures (see Berlanga, et al., Small, 2011, 7, 1207). Mechanical grinding-induced delamination of chemically stable porous COFs synthesized using solvothermal condensation reaction of 2,4,6-triformylphloroglucinol with various diamines has also been shown to generate covalent organic nanosheets (see Chandra, et al., J. Am. Chem. Soc., 2013, 135, 17853). Chemical exfoliation of anthracene-based COFs, synthesized by solvothermal condensation of 2,6-diaminoanthracene with 2,4,6-triformylphloroglucinol, also led to exfoliated nanosheets (see Khayum, et al., Angew. Chem. Int. Ed., 2016, 55, 15604). Nanosheets of such exfoliated COFs have applications as charge carriers (see Sun, et al., J. Phys. Chem. C., 2016, 120, 14706) and anode materials for Li-ion batteries (see (a) Haldar, et al., Adv. Energy Mater., 2018, 8, 1702170; (b) Wang, et al., J. Am. Chem. Soc., 2017, 139, 4258).

[0005] Most of the existing exfoliation methods suffer from drawbacks such as non-uniformity with respect to sheet thickness, energy-costly methods, chemical modifications that lead to material property changes or damage, use of environmentally harmful strategies, etc. Thus, there is an unmet need to provide a safe, green and energy-efficient protocol for the exfoliation of COFs into ultrathin nanosheets.

[0006] By introducing suitable CO2 reactive sites into 2D COFs, not only can CO2 gas be stored, but also its effective conversion or utilization for highly desirable antibacterial properties can be achieved without generating substantial antibiotic resistance. Tertiary amines react with CO2 in water to form bicarbonate and quaternary ammonium species, which revert to neutral amines upon heating in the presence of an inert gas such as argon (see (a) Lee, et al., Chem. Commun., 2015, 51, 2036; (b) Guo, et al., Adv. Mater., 2012, 3, 584; (c) Che, et al., Angew. Chem. Int. Ed., 2015, 54, 8934). Several reports have reported on the storage of carbon dioxide in COFs ((a)Babaroa, et al., Exceptionally high CO2storage in covalent-organic frameworks: Atomistic simulation study, Energy Environ. Sci., 2008,1, 139-143;(b)Ozedemir, et al. Covalent Organic Frameworks for the Capture, Fixation, or Reduction of CO2, Front. Energy Res., 2019, 7, 77;(c)Zeng, et al. Covalent Organic Frameworks for CO2Capture, Adv. Mater., 2016, 28, 2855-2873;(d)Furukawa, et al. Storage of Hydrogen, Methane, and Carbon Dioxide in Highly Porous Covalent Organic Frameworks for Clean Energy Applications, J. Am. Chem. Soc. 2009, 131, (See 8875-8883.)It has also been reported that several COFs possess antibacterial activity (see (a) Wan, et al., Microporous Frameworks as Promising Platforms for Antibacterial Strategies Against Oral Diseases, Front. Bioeng. Biotechnol., 2020, 8, 628; (b) Bhunia, et al., 2D Covalent Organic Frameworks for Biomedical Applications, Adv. Funct. Mater., 2020, 30, 2002046).

[0007] The synthesis and application of COFs have been reported in several patents. US20140148596A1 (Dichtel, et al.) discloses the synthesis of crystalline COFs containing phthalocyanine moieties and boron-containing polyfunctional linking groups linked by boronic ester bonds, along with their application in electronic materials. WO2014 / 057504A1 (Banerjee, et al.) reports COFs synthesized by mechanochemical / solvothermal methods utilizing mechanical grinding, which exhibit stability to acidic, basic and neutral conditions, and delamination into several layers of covalently bonded organic nanosheets. Chemically stable hollow sphere-shaped covalently bonded organic frameworks with mesoporous walls with high surface area, their synthesis process and their adsorption capabilities are disclosed by US10,266,634 (Banerjee, et al.). US20190161623 disclosed a method for modifying COFs containing imine groups using phenylacetylene to convert the imine groups into quinoline groups, and their superhydrophobic properties.

[0008] Tertiary amine-containing COFs based on 2,5-bis(2-(dimethylamino)ethoxy)terephthalohydrazide and their carbon dioxide sorption properties have been reported, but these sorption properties have been evaluated in the solid state without self-exfoliation. These COFs have also not been shown to possess antibacterial activity (see Gottschling, et al., Molecular Insights into Carbon Dioxide Sorption in Hydrazone-Based Covalent Organic Frameworks with Tertiary Amine Moieties, Chem. Mater. 2019, 31, 1946-1955). No 2D COFs constructed from building blocks with tertiary amine functional units have been found in the literature that have suitable CO2 adsorption capacity while simultaneously reversible exfoliation and switchable antibacterial activity. Such COFs could provide an ideal "on / off antibacterial switch" based platform by generating a CO2-mediated temporary charge that can be neutralized again by removing the CO2 gas from the medium.

[0009] Based on extensive research related to the exfoliation of porous organic frameworks, the present inventors found that most of the existing exfoliation methods suffer from drawbacks such as non-uniformity in terms of sheet thickness, energy-costly methods, chemical modifications that result in material property changes or damage, use of environmentally harmful strategies, etc. Thus, there is an unmet need to provide a safe, environmentally friendly and energy-efficient protocol for the exfoliation of COFs into ultrathin nanosheets. Summary of the Invention [Problem to be solved by the invention]

[0010] The main objective of this invention is the design and development of an economical and environmentally friendly process for the self-exfoliation of 2D covalent organic frameworks using reversible adsorption of carbon dioxide.

[0011] Another objective is to generate temporary surface charges in COF structures bearing multiple dimethylamino groups capable of trapping carbon dioxide at ambient temperature and pressure, leading to the subsequent self-exfoliation of the COFs into ultrathin nanosheets by trapping carbon dioxide under humid conditions.

[0012] Yet another object of the present invention is to provide a smart material with tunable antibacterial activity against pathogenic bacteria, where the carbon dioxide induced delamination process is fully reversible upon heat treatment and control over bacterial growth is achieved via an efficient antibacterial switch.

[0013] Yet another object of the present invention is to make functional groups within the COFs available for interaction with carbon dioxide resulting in the generation of ionic groups on their surface, thereby providing functional group availability that enables the subsequent self-exfoliation of COFs into ultrathin nanosheets. [Means for solving the problem]

[0014] The present invention provides a process for the exfoliation of porous organic compounds, particularly covalent organic frameworks (COFs), using carbon dioxide in the presence of water, moisture or humidity, which results in the capture of a minimum of 0.4 mmol / g of carbon dioxide under ambient conditions at room temperature and atmospheric pressure, thereby inducing smart and switchable antimicrobial activity.

[0015] Thus, the present invention provides a two-dimensional porous crystalline stable covalent organic framework (COF) of formula I

[0016] [ka] Formula I (wherein R=NMe2 or Et).

[0017] In yet another embodiment of the invention, said COF comprises of a single or multiple dimethylamino groups.

[0018] In yet another embodiment, the present invention provides a process for the preparation of a covalent organic framework (COF) of formula I disclosed herein, comprising: i. synthesizing hydrazides of formula A using intermediates of formula 2, formula 3, and formula 5

[0019] [ka] where R=NMe2 or Et, ii. charging a Teflon-lined steel bomb with 1 equivalent of aldehyde and 1.5 equivalents of hydrazide of formula A obtained in step (i) to obtain a mixture; iii. adding mesitylene, 1,4-dioxane and acetic acid to the mixture obtained in step (ii) to obtain a mixture; iv. sonicating the mixture obtained in step (iii) for a period ranging from 5 to 10 minutes to get a homogenous dispersion; v. A process of sealing the Teflon-coated steel pressure vessel and heating it at a temperature in the range of 100 to 120°C for 3 days; vi. Recovering the precipitate by centrifugation at a speed in the range of 500 to 1500 rpm for a period in the range of 1 to 10 minutes; vii. washing the precipitate obtained in step (vi) with water; viii. purifying by Soxhlet extraction using acetone, tetrahydrofuran, and methanol; ix. Drying the powder under vacuum at a temperature in the range of 50-100° C. for a period in the range of 1-24 hours to obtain the covalent organic framework (COF) of formula I. The present invention provides a process including:

[0020] In yet another embodiment of the present invention, the aldehyde used is selected from aromatic trialdehydes, preferably 2,4,6-triformylphloroglucinol.

[0021] In yet another embodiment of the present invention, the hydrazide of formula A used is selected from aromatic terephthalohydrazides, preferably 2,5-bis(3-dimethylamino)propoxyterephthalohydrazide or 2,5-bis(pentyloxy)terephthalohydrazide.

[0022] In yet another embodiment, the present invention provides a process for reversible self-exfoliation of the covalent organic frameworks (COFs) disclosed herein, comprising: i. dispersing or suspending the COF in water at a w / v ratio in the range of 1 to 10 mg / mL to obtain a dispersion; ii. purging the dispersion obtained in step (i) with a balloon filled with carbon dioxide at atmospheric pressure and at a temperature in the range of 25-32° C. for a period in the range of 10-30 minutes to obtain exfoliated ultrathin nanosheets, thereby generating ionic charges on the COFs surface, and the zeta potential of said COFs is greater than 20 mV, preferably greater than 30 mV; The present invention provides a process including:

[0023] In yet another embodiment of the present invention, the generation of ionic surface charges leads to the self-exfoliation or delamination of said COFs into ultrathin nanosheets.

[0024] In yet another embodiment of the invention, the nanosheets have a uniform thickness and are less than 5 nm, preferably less than 2 nm, and the ultrathin nanosheets are composed of at most a single or double layer of COFs.

[0025] In yet another embodiment of the invention, the process is specific for the combination of COFs containing single or multiple dimethylamino groups with carbon dioxide, whereby the use of other gases, particularly argon, nitrogen, hydrogen, etc., does not result in either or all of the induction of ionic charge or self-exfoliation or delamination of COFs with or without dimethylamino groups.

[0026] In yet another embodiment of the present invention, carbon dioxide is adsorbed onto the exfoliated COFs, which is thermoreversible by mild heat treatment in the presence of argon at a temperature in the range of 30-50° C. for a period in the range of 5-10 minutes, whereby removal of the adsorbed carbon dioxide leads to neutralization of the surface charge, returning the zeta potential value to near zero and restoring the initial multilayered morphology of the COFs.

[0027] In yet another embodiment of the present invention, ultrathin nanosheets of self-exfoliated COFs possess tunable antibacterial activity against both Gram-positive and Gram-negative bacteria, with bacterial growth reduced by more than 60% within 30 minutes of incubation with exfoliated COFs (1.0 mg / mL) and bacterial growth reduced by more than 90% within 120 minutes of incubation with exfoliated COFs (1.0 mg / mL), and further, said antibacterial activity of COFs is reversible upon heat treatment, with less than 30% reduction in bacterial growth under the same conditions.

[0028] These and other features, aspects, and advantages of the present subject matter will become better understood with reference to the following description and appended claims. This Summary is provided to introduce a selection of concepts in a simplified form. It is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 shows the molecular structures of COFs 1 and 2, according to one embodiment of the present disclosure. [Diagram 2]FIG. 2 shows a packing model for COF-1, according to one embodiment of the present disclosure. [Diagram 3] FIG. 3 shows a packing model for COF-2, according to one embodiment of the present disclosure. [Figure 4] FIG. 4 shows the measured and predicted XRD [X-ray diffraction] patterns of COF-1, supporting the overlapping packing model shown in FIG. 2, according to one embodiment of the present disclosure. [Diagram 5] FIG. 5 shows the measured and predicted XRD patterns of COF-2, supporting the overlapping packing model shown in FIG. 3, according to one embodiment of the present disclosure. [Figure 6] FIG. 6 shows thermogravimetric analysis of COFs 1 and 2, confirming their thermal stability up to at least 350° C., according to one embodiment of the present disclosure. [Figure 7] FIG. 7 shows the FT-IR [Fourier transform infrared] spectrum of COF-1, according to one embodiment of the present disclosure. [Figure 8] FIG. 8 shows the FT-IR spectrum of COF-2, according to one embodiment of the present disclosure. [Figure 9] FIG. 9 shows 13C CP-MAS [cross polarization-magic angle spinning] NMR [nuclear magnetic resonance] spectra of COF-1 (bottom) and COF-2 (top), according to one embodiment of the present disclosure. [Figure 10] FIG. 10 shows the CO2 adsorption profile of COF-1 at 303 K, confirming the adsorption capacity of 0.4 mmol / g, according to one embodiment of the present disclosure. [Figure 11] FIG. 11 shows the carbon dioxide induced reaction of the tertiary amine groups of COF-1 and the formation of surface charges according to one embodiment of the present disclosure. [Figure 12] FIG. 12 shows a graph of the zeta potential of exfoliated COF-1 after purging with CO 2 , illustrating the induction of surface ionic charge, according to one embodiment of the present disclosure. [Figure 13] FIG. 13 shows transmission electron micrographs of the exfoliation process of COF-1 upon carbon dioxide purging, revealing ultrathin nanosheets with few-layer structure morphology, according to one embodiment of the present disclosure. [Figure 14] FIG. 14 shows a transmission electron micrograph of COF-1 nanosheets with 1-2 layer structure morphology obtained by exfoliation of COF-1 upon carbon dioxide purging, according to one embodiment of the present disclosure. [Figure 15] FIG. 15 shows (a), (b) atomic force micrographs of ultrathin nanosheets obtained by exfoliation of COF-1 upon carbon dioxide purging according to one embodiment of the present disclosure, and (c), (d) height profiles of the corresponding white lines drawn on (a) and (b) representing a thickness of 1 nm suggesting a few-layer structure. [Figure 16] FIG. 16 shows a Raman spectrum of exfoliated ultrathin nanosheets of COF-1 deposited on an ITO surface in the presence of gold, indicating the presence of bicarbonate ions, supporting the mechanism of exfoliation suggested in FIG. 22, according to one embodiment of the present disclosure. [Figure 17] FIG. 17 shows the experimental setup for a CO 2 purging experiment (left) and a close-up of the circled area (right), according to one embodiment of the present disclosure. [Figure 18] FIG. 18 shows the Tyndall effect of exfoliated ultrathin nanosheets of COF-1, according to one embodiment of the present disclosure. [Figure 19] FIG. 19 shows (a) a daylight picture of COF-2 stored in water before CO2 purging and (b) the absence of Tyndall effect after CO2 purging, confirming that negligible delamination occurs in this case, according to one embodiment of the present disclosure. [Figure 20] FIG. 20 shows the reversible induction of surface ionic charge in COF-1 according to one embodiment of the present disclosure, with the exfoliated COF exhibiting a zeta potential greater than 32 mV and the heated / argon treated exfoliated COF reverting to the original COF with a zeta potential close to zero. [Figure 21] FIG. 21 shows a TEM image illustrating the reversible exfoliation of COF-1, where the heated / argon treated exfoliated COF reconstructs back to the original COF with a multilayer structure, according to one embodiment of the present disclosure. [Figure 22]FIG. 22 shows the antibacterial activity of carbon dioxide alone, pristine COF-1, and carbon dioxide-treated exfoliated COF nanosheets with ionic surface charges (E. coli), according to one embodiment of the present disclosure. [Figure 23] FIG. 23 shows photographs depicting CFUs [Colony Forming Units] of E. coli after 120 minutes of treatment with (A) control, (B) carbon dioxide only, and (C) exfoliated ultrathin nanosheets of COF-1, according to one embodiment of the present disclosure. [Figure 24] FIG. 24 shows photographs depicting CFU of E. coli after 30 and 60 minutes of treatment under various conditions, according to one embodiment of the present disclosure. [Diagram 25] FIG. 25 shows the antibacterial activity of carbon dioxide-treated exfoliated COF nanosheets with ionic surface charges according to one embodiment of the present disclosure and its reversibility upon heat / argon treatment, thereby enabling a smart antibacterial switch against E. coli. [Figure 26] FIG. 26 shows the antibacterial activity of carbon dioxide treated exfoliated COF nanosheets with ionic surface charges according to one embodiment of the present disclosure and its reversibility upon heat / argon treatment, thereby enabling a smart antibacterial switch against E. coli, demonstrating an ideal “on / off antibacterial switch” based platform. [Figure 27] 27 shows the antibacterial activity of carbon dioxide treated exfoliated COF nanosheets with ionic surface charge and its reversibility upon heat / argon treatment, thereby enabling a smart antibacterial switch against E. coli: (A) control, (B) exfoliated nanosheets of COF-1 obtained by purging with CO2 and (C) reconstituted COF-1 obtained by treating with heat / argon according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Those skilled in the art will recognize that the present disclosure may be modified and altered other than those specifically described. It should be understood that the present disclosure includes all such variations and modifications. The present disclosure also includes all such steps, features, compositions, and compounds mentioned or shown herein, individually or collectively, and also includes any combination of any or more of such steps or features.

[0031] The invention will now be described in detail with reference to certain preferred embodiments thereof so that its various aspects may be more fully understood and appreciated.

[0032] For convenience, before further description of the present disclosure, certain terms used in the present specification and examples are clarified here.These definitions should be interpreted in light of the remaining parts of the present disclosure and should be understood by those skilled in the art.Terms used in the present specification have meanings that are recognized and known to those skilled in the art, but for convenience and completeness, certain terms and their meanings are described below.

[0033] definition For convenience, before further description of the present disclosure, certain terms used in the present specification and examples are clarified here.These definitions should be interpreted in light of the remaining parts of the present disclosure and should be understood by those skilled in the art.Terms used in the present specification have meanings that are recognized and known to those skilled in the art, but for convenience and completeness, certain terms and their meanings are described below.

[0034] The articles "a", "an" and "the" are used to refer to one or to more than one (i.e. to at least one) of the grammatical object of the article.

[0035] The terms "comprise" and "comprising" are used in an inclusive and open-ended sense to mean that additional elements may be included. It is not intended to be interpreted as "consists of only."

[0036] Throughout this specification, unless the context otherwise requires, the word "comprise", and variations such as "comprises" and "comprising", will be understood to mean the inclusion of a stated element or step or elements or steps but not to the exclusion of other elements or steps or elements or steps.

[0037] The present invention provides an economical and environmentally friendly process for the self-exfoliation of 2D covalent organic frameworks bearing multiple dimethylamino groups capable of capturing carbon dioxide at ambient temperature and pressure.

[0038] Furthermore, the present invention provides functional group availability within the COFs for interaction with carbon dioxide resulting in the generation of ionic groups on their surface, thereby allowing the process to subsequently self-exfoliate the COFs into ultrathin nanosheets.

[0039] The present invention also contemplates providing an antibacterial smart COF with tunable antibacterial activity, in which carbon dioxide induced detachment is fully reversible upon warming and bacterial growth is regulated by a smart and efficient antibacterial switch.

[0040] The present invention aims to provide a process for the reversible self-exfoliation of porous organic compounds, in particular covalent organic frameworks (COFs), using carbon dioxide under ambient conditions in the presence of water, moisture or humidity, said COFs comprising single or multiple dimethylamino groups.

[0041] Another crucial component of the present invention is that when dispersed or suspended in water and purged with a carbon dioxide filled balloon for 10-30 minutes under ambient conditions, ionic charges are generated on the COF surface such that the zeta potential of the COF is greater than 30 mV and the COF self-exfoliates or delaminates into ultra-thin nanosheets with uniform thickness of less than 2 nm, which consist of up to a single or double layer of COF.

[0042] The process is specific for the combination of COFs containing single or multiple dimethylamino groups with carbon dioxide; other gases, such as argon, nitrogen, hydrogen, etc., do not result in the induction of ionic charges or self-exfoliation or delamination of the COFs.

[0043] Carbon dioxide adsorption on the exfoliated COFs is thermoreversible by mild heat treatment in the presence of argon at temperatures ranging from 30 to 50°C for 5 to 10 minutes, whereby removal of the adsorbed carbon dioxide leads to neutralization of the surface charge, the zeta potential value returns to near-zero values, and the initial multilayered morphology of the COFs is restored, whereby the ultrathin nanosheets of self-exfoliated COFs possess tunable antibacterial activity against both Gram-positive and Gram-negative bacteria, and further, the antibacterial activity of the COFs is reversible upon heat treatment.

[0044] Another important aspect of the present invention discloses the use in household, industrial or automotive coatings and in personal protective equipment, particularly air filters, membranes, for continuous air cleaning using reversible carbon dioxide sorption and switchable antimicrobial activity, where adsorption of carbon dioxide in the presence of water, moisture or humidity turns on the antimicrobial activity, and further increase in temperature above room temperature resets the process, resulting in the release of carbon dioxide and a reduction in antimicrobial activity, thereby switching the material into a ready mode for another cycle of carbon dioxide adsorption and resulting antimicrobial action.

[0045] Although the subject matter has been described in some detail with reference to certain examples and embodiments thereof, other configurations are possible. EXAMPLES

[0046] [Example 1] Synthesis of diethyl 2,5-bis(3-bromopropoxy)benzene-1,4-dicarboxylate [2]

[0047] [ka]

[0048] 1,3-Dibromopropane (4.38 mL, 10 mmol), TBAB (0.1 g, 0.31 mmol) and K2CO3 (2.16 g, 15.6 mmol) were placed in a 250 mL two-necked round bottom flask containing 40 mL of anhydrous acetone. The mixture was stirred at room temperature (25-32 °C) for 30 min and 5-dihydroxybenzene-1,4-dicarboxylate 1 (2.04 g, 8 mmol) was added dropwise. The reaction mixture was refluxed at 80 °C for 24 h. After the reaction mixture was cooled to room temperature (25-32 °C), the solvent was evaporated under reduced pressure. The residue thus obtained was extracted using chloroform, washed with water, brine and dried over anhydrous sodium sulfate. The crude product was subjected to column chromatography on silica gel (60% chloroform / hexane) to obtain the pure product. Yield: 85%; 1 H NMR (500 MHz, CDCl3): δ = 7.26 (s, 2H), 4.39-4.35 (m, 4H), 4.17-4.15 (t, 4H), 3.67-3.65 (t, 4H), 2.36-2.31 (m, 4H), 1.41-1.38 (m, 6H) ppm; ESI-MS (m / z): [M+Na] + C 18 H 24 Calculated for Br2O6: 516.994; Found: 516.993. [Example 2]

[0049] Synthesis of 2,5-bis[3-(dimethylamino)propoxy]benzene-1,4-dicarboxylate[3]

[0050] [ka]

[0051] Compound 2 (500 mg, 4.8 mmol) was placed in a 100 mL round bottom flask and 10 mL of a solution of dimethylamine in THF (2.0 M) was added to it. The reaction mixture was heated to reflux at 80° C. for 12 h. After the reaction mixture was cooled to room temperature, the solvent was evaporated. The residue was extracted using chloroform. The organic layer was washed with water, brine, dried over anhydrous sodium sulfate, and the solvent was evaporated under reduced pressure to obtain the crude product. This crude product was used for the next reaction without further purification. Yield: 80%; 1 H NMR (500 MHz, MeOD): δ = 7.66 (s, 2H), 4.45-4.41 (m, 4H), 4.35-4.33 (t, 4H), 3.51-3.49 (t, 4H), 3.04-3.03 (s, 12H), 2.36-2.31 (m, 4H), 1.43-1.40 (t, 6H) ppm; ESI-MS (m / z): [M+Na] + C 22 H 36 Calculated N2O6: 448.257; Measured: 448.268. [Example 3]

[0052] Synthesis of 2,5-bis(3-dimethylamino)propoxyterephthalohydrazide [4]

[0053] [ka]

[0054] Compound 3 (330 mg, 4.8 mmol) and hydrazine hydrate (2 mL, 9.32 mmol) were placed in a 100 mL two-neck round-bottom flask containing 20 mL of absolute ethanol. The reaction mixture was refluxed at 80° C. for 12 h. After cooling to room temperature, the product was allowed to settle for precipitation. The white precipitate was collected by filtration, washed with water, and dried under vacuum to obtain 0.264 g (yield: 80%) of a white solid. mp: 148-152° C.; 1 H NMR (500 MHz, DMSO-d6): δ = 9.57 (s, 2H), 7.44 (s, 2H), 4.59 (m, 4H), 4.11-4.08 (t, 3H), 2.50-2.49 (m, 12H), 2.39-2.36 (t, 4H), 1.90-1.85 (m, 4H) ppm; 13 C NMR (125 MHz, CDCl3): δ = 168.75, 154.96, 129.74, 119.82, 79.23, 61.56, 60.08, 90.31, 31.36 ppm; ESI-MS (m / z): [M+Na] + C 18 H 32 Calculated value for N6O4: 419.248; Found value: 419.254. [Example 4]

[0055] Synthesis of 2,5-dipentoxybenzene-1,4-dicarboxylate [5]

[0056] [ka]

[0057] 1-Bromopentane (1.5 mL, 8.1 mmol) and K2CO3 (2.16 g, 15.6 mmol) were placed in a 250 mL two-necked round-bottom flask containing 40 mL of anhydrous acetonitrile. The mixture was stirred at room temperature [25 °C] for 30 min and 5-dihydroxybenzene-1,4-dicarboxylate 1 (2.04 g, 8 mmol) was added dropwise. The reaction mixture was refluxed at 80 °C for 24 h. After the reaction mixture was cooled to room temperature, the solvent was evaporated under reduced pressure. The residue thus obtained was extracted using chloroform, washed with water, brine, and dried over anhydrous sodium sulfate. The crude product was subjected to column chromatography on silica gel (60% chloroform / hexane) to obtain the pure product. Yield: 85%; 1 H NMR (500 MHz, CDCl3): δ = 7.26 (s, 2H), 4.29-4.25 (q, 4H), 3.92-3.90 (t, 4H), 1.72-1.68 (m, 4H), 1.38-1.34 (m, 4H), 1.30-1.26 (m, 10H) ppm, 0.84-0.81 (t, 6H); ESI-MS (m / z): [M]C 22 H 34 Calculated O6 value: 394.223; measured value: 394.228. [Example 5]

[0058] Synthesis of 2,5-bis(pentyloxy)terephthalohydrazide [6]

[0059] [ka]

[0060] Compound 5 (1 g, 2.534 mmol) and hydrazine hydrate (8 mL, 253 mmol) were placed in a 100 mL two-neck round-bottom flask containing 40 mL of absolute ethanol. The reaction mixture was refluxed at 80° C. for 12 h. After cooling to room temperature, the reaction mixture was allowed to stand and the product precipitated. The white precipitate formed was collected by filtration, washed with water, and dried under vacuum to give a white solid, 0.856 g (yield: 85%). mp: 139-143° C.; 1H NMR (500 MHz, DMSO-d6): δ = 9.28 (s, 2H), 7.39 (s, 2H), 4.58 (m, 4H), 4.07-4.05 (t, 3H), 3.47-3.42 (m, 4H), 1.40-1.34 (m, 8H), 0.92-0.87 (t, 6H) ppm; 13 C NMR (125 MHz, DMSO-d6): δ = 169.09, 154.95, 130.16, 119.93, 74.35, 61.24, 45.32-44.32, 33.41-32.81, 2.06, 23.76, 19.11 ppm; ESI-MS (m / z): [M+H] + C 18 H 30 Calculated N4O4: 366.226; Measured: 367.233. [Example 6]

[0061] Synthesis of COF-1 (R=NMe2) A Teflon-coated steel pressure vessel was charged with 2,4,6-triformylphloroglucinol (63 mg, 0.3 mmol), 4 (178.416 mg, 0.45 mmol), 1.5 mL mesitylene, 1.5 mL 1,4-dioxane, and 0.5 mL 6 M aqueous acetic acid. The mixture was sonicated for 10 min to obtain a homogenous dispersion. The Teflon-coated steel pressure vessel was then sealed and heated at 120 °C for 3 days. The brown precipitate was collected by centrifugation and washed repeatedly with double-distilled water. The collected powder was then purified by Soxhlet extraction using a series of solvents, including acetone, tetrahydrofuran, and methanol. The resulting solid was then dried at 100 °C under vacuum for 24 h to obtain COF-1 as a dark brown powder in 85% isolated yield. FT-IR (KBr):ν max =3040(w),1658(m),1603(m),1593(w),1534(s),1486(s),1434(s),1327(m ),1284(m),1213(m),1131(w),1041(w),962(w),899(w),804(w),776(w)cm -1 ; 13C CP-MAS NMR (100.61 MHz, solid state): δ = 181.44, 159.79, 149.36, 120.765, 114.12, 99.51, 66.73, 54.85, 43.01 and 24.18 ppm. [Example 7]

[0062] Synthesis of COF-2 (R=Et) A Teflon-coated steel pressure vessel was charged with 2,4,6-triformylphloroglucinol (63 mg, 0.3 mmol), 6 (158.139 mg, 0.45 mmol), 1.5 mL mesitylene, 1.5 mL 1,4-dioxane, and 0.5 mL 6 M aqueous acetic acid. The mixture was sonicated for 10 min to obtain a homogenous dispersion. The Teflon-coated steel pressure vessel was then sealed and heated at 120 °C for 3 days. The pale yellow color was collected by centrifugation and washed repeatedly with double distilled water. The collected powder was then purified by Soxhlet extraction using a series of solvents such as acetone, tetrahydrofuran, and methanol. The resulting solid was then dried at 100 °C under vacuum for 24 h to obtain COF-2 as a pale yellow powder with an isolated yield of 80%. FT-IR (KBr):ν max =3410(w),2956(w),2930(w),2867(w),1680(s),1633(s),1592(w),1537(s),1521(s),14 85(s),1456(s),1414(m),1385(w),1320(m),2214(s),1188(s),1126(w),1006(w),899(w) 810(w),771(w)cm -1 ; 13 C CP-MAS NMR (100.61 MHz, solid state): δ = 170.01, 160.98, 157.46, 149.01, 144.12, 121.46, 114.47, 98.80, 69.15, 27.66, 21.72 and 12.34 ppm. [Example 8]

[0063] Carbon dioxide purge experiment and self-peeling of COF COFs 1 and 2 (2 mg) were suspended in DI water (4 mL) and purged with CO2 for 30 min using a CO2-filled balloon. After 30 min of purging, the Tyndall effect was observed for COF-1. Similar purging with other gases such as Ar, N2 did not show the Tyndall phenomenon, demonstrating the specificity of COF-1 for CO2. The Tyndall effect exhibited by COF-1 in water suggested the presence of exfoliated ultrathin nanosheets, which was supported by morphological analysis. COF-2 did not show the Tyndall effect under similar conditions, supporting the role of N(Me)2 groups in the exfoliation process. [Example 9]

[0064] Antibacterial test using peeled COF Single colonies of E. coli and S. aureus were transferred from nutrient agar (NA) plates to 10 mL of nutrient medium and grown for 24 h at 37°C. The bacteria were then harvested by centrifugation at 8000 rpm for 5 min and washed twice with phosphate-buffered saline (PBS, pH=7.2±0.2). The supernatant was discarded and the remaining bacterial cells were resuspended in PBS and incubated at an optical density of 1.0 at 600 nm (OD 600 =1.0). The bacteria were then incubated in the dark at 37°C for 16 hours with COF (purged with carbon dioxide). After incubation, all bacterial suspensions were diluted to 1 x 10 with PBS. 8 The bacteria were serially diluted 2-fold. 100 μL of the bacterial dilutions were streaked onto NA plates, and the colonies formed after 24 h of incubation at 37° C. were counted as colony forming units (CFU). Untreated bacterial solution was used as control. The experiment was performed in triplicate. (Advantages of the invention)

[0065] · Economical and environmentally friendly process for self-peeling of COFs Use of carbon dioxide, an inexpensive reagent Highly reversible process Adjustable antibacterial activity The presence of ionic charges that can be generated in situ Potential applications in antibacterial coatings, PPE, etc.

Claims

1. Two-dimensional porous crystalline stable covalent organic frameworks (COFs) of formula I 【Chemistry 1】 Formula I (In the formula, R=NMe 2 or Et).

2. 2. The covalent organic framework (COF) of claim 1, comprising a single or multiple dimethylamino groups.

3. A process for the preparation of a covalent organic framework (COF) of formula I according to claim 1, comprising: i. synthesizing hydrazides of formula A using intermediates of formula 2, formula 3, and formula 5 【Chemistry 2】 (In the formula, R=NMe 2 or Et), ii. charging a Teflon-lined steel pressure vessel with 1 equivalent of aldehyde and 1.5 equivalents of the hydrazide of formula A obtained in step (i) to obtain a mixture; iii. adding mesitylene, 1,4-dioxane and acetic acid to the mixture obtained in step (ii) to obtain a mixture; iv. sonicating the mixture obtained in step (iii) for a period ranging from 5 to 10 minutes to obtain a homogenous dispersion; v. sealing the Teflon-coated steel pressure vessel and heating at a temperature in the range of 100-120° C. for 3 days; vi. Recovering the precipitate by centrifugation at a speed ranging from 500 to 1500 rpm for a period ranging from 1 to 10 minutes; vii. washing the precipitate obtained in step (vi) with water; viii. purifying by Soxhlet extraction using acetone, tetrahydrofuran, and methanol; and ix. Drying the powder under vacuum at a temperature ranging from 50 to 100° C. for a period ranging from 1 to 24 hours to obtain the covalent organic framework (COF) of formula I. The process includes:

4. 4. The process according to claim 3, wherein the aldehyde used is selected from aromatic trialdehydes, preferably 2,4,6-triformylphloroglucinol.

5. 4. The process according to claim 3, wherein the hydrazide of formula A used is selected from aromatic terephthalohydrazides, preferably 2,5-bis(3-dimethylamino)propoxyterephthalohydrazide or 2,5-bis(pentyloxy)terephthalohydrazide.

6. A process for reversible self-exfoliation of the covalent organic framework (COF) of claim 1, comprising: i. dispersing or suspending COF in water at a w / v ratio in the range of 1-10 mg / mL to obtain a dispersion; ii. Purging the dispersion obtained in step (i) with a balloon filled with carbon dioxide at a temperature in the range of 25-32° C. and at atmospheric pressure for a period in the range of 10-30 minutes to obtain exfoliated ultrathin nanosheets, thereby generating ionic charges on the COF surface, and the zeta potential of the COFs is greater than 20 mV, preferably greater than 30 mV. The process includes:

7. The process of claim 6, wherein the generation of ionic surface charges results in the self-exfoliation or delamination of the COFs into ultrathin nanosheets.

8. 7. The process of claim 6, wherein the thickness of the nanosheets is uniform and less than 5 nm, preferably less than 2 nm, and the ultrathin nanosheets are composed of at most a single or double layer of the COFs.

9. 7. The process of claim 6, wherein the process is specific for the combination of COFs containing single or multiple dimethylamino groups with carbon dioxide, whereby the use of other gases, in particular argon, nitrogen, hydrogen, etc., does not result in either or all of the induction of ionic charge or self-exfoliation or delamination of the COFs, with or without dimethylamino groups.

10. 7. The process of claim 6, wherein carbon dioxide is adsorbed onto the exfoliated COFs, which is thermoreversible by mild heat treatment in the presence of argon at a temperature in the range of 30-50° C. for a period in the range of 5-10 minutes, whereby removal of the adsorbed carbon dioxide results in neutralization of the surface charge, returning the zeta potential value to a value close to zero and restoring the initial multilayered morphology of the COFs.